Experimental and theoretical insights into sustained water splitting with an electrodeposited nanoporous nickel hydroxide@nickel film as an electrocatalyst. Issue 17 (11th April 2017) - Xing, Zhicai; Gan, Linfeng; Wang, Jin; Yang, Xiurong
Abstract : Electrodeposited nanoporous Ni(OH)2 @Ni film acts as a Janus electrocatalyst for the hydrogen evolution and oxygen evolution reaction, and overall water splitting, exhibiting superior activities and exceptional long-term stability. Theoretical calculations show that the synergistic electrocatalytic effects of Ni(OH)2 and Ni are responsible for the high activities. Abstract : The execution of the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) requires active, low-cost, and earth-abundant electrocatalysts to realize large-scale water splitting. Herein, by utilization of the electrodeposition technique, a new category of nickel-based materials, i.e. nanoporous nickel hydroxide@nickel (Ni(OH)2 @Ni) films on carbon cloth (Ni(OH)2 @Ni/CC), has been reported as a Janus electrocatalyst for overall water splitting. The as-deposited Ni(OH)2 @Ni/CC exhibited remarkable catalytic performance for the HER in alkaline electrolytes with an overpotential of 68 mV needed to drive the current density of 10 mA cm −2 and much better durability than Pt/C. This film is also efficient for catalyzing the OER in basic media. These films can be employed as catalysts on both the anode and cathode for overall water splitting that approaches 10 mA cm −2 at a cell voltage of 1.58 V, with catalytic stability exceeding those with RuO2 and Pt/C catalysts. Density functional theory calculations further demonstrate that the Ni(OH)2 and Ni in Ni(OH)2 @Ni films synergistically favor the chemisorption of hydrogen-containing intermediates, thus leading to highly enhanced water splitting activity.